The analysis of stability and variability of metrological characteristic (conversion coefficient) of glass capillary reference viscometers - V. Sh. Sulaberidze; А. А. Neklyudova (Омский научный вестник)
The results of determining the stability and variability of the main characteristic of glass capillary reference viscometers — conversion coefficient — by analyzing a set of data on viscometers having different diameters of the measuring capillary are presented. It is shown that the mean values of the sample differ from the mean values of the symmetric normal distribution curves within (2–4) %, as well as the correspondence of statistics to the normal distribution law by means of the inverse standard function and histograms showing the degree of correspondence of the sample distribution to the theoretical one.